Histone ZmH2B regulates resistance to the Southern corn leaf blight pathogen Bipolaris maydis in maize - Ding, Ying; Wu, Hongliang; Ning, Na; Yu, Haiyue; Liu, Chaotian; Lv, Ruoya; Li, Shu; Hao, Junjie; Wang, Xintao; Zhang, Xuecai; Xie, Xin; Li, Xinfeng; et al. (BioMed Central Ltd., 2025)
Background: H2B histones play crucial roles in plant responses to biotic stress. However, to date, most research on H2B histones has focused on their roles in post-translational modification, and studies specifically investigating the intrinsic properties of these histones remain relatively limited. Here we identified the ZmH2B in maize (Zea mays) and investigated its role in the response of maize to infection by the Southern corn leaf blight pathogen Bipolaris maydis. Result: In this study, a nucleus-localized ZmH2B was identified from maize. To characterize the role of this histone in disease resistance, we employed virus-induced gene silencing (VIGS) and transient overexpression (VOX) to generate ZmH2B-silenced (FoMV:ZmH2B) and ZmH2B-overexpressing (FoMV:ZmH2B-VOX) lines. FoMV:ZmH2B lines showed enhanced B. maydis infection and an inhibited chitin-induced reactive oxygen species burst, whereas FoMV:ZmH2B-VOX lines exhibited the opposite effects. Furthermore, ZmH2B overexpression induced the expression of various pathogenesis-related genes, suggesting that these genes enhance resistance against B. maydis. Transcriptome analysis of ZmH2B-silenced plants revealed that the differentially expressed genes were predominantly enriched in photosynthesis-related pathways, pointing to a role for photosynthesis in B. maydis resistance. Conclusions: These results suggest that ZmH2B positively regulates maize resistance to B. maydis.